2018
DOI: 10.1111/tri.13323
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol versus placebo for reduction of proteinuria in kidney transplant recipients: a double-blind, randomized controlled trial

Abstract: Proteinuria after kidney transplantation is accompanied by an increased risk of graft failure. In this single-center, placebo-controlled, double-blind trial we studied whether vitamin D receptor activator paricalcitol might reduce proteinuria. Patients with urinary protein-to-creatinine ratio (UPCR) ≥20 mg/mmol despite optimization of the renin angiotensin aldosterone system (RAAS) blockade were randomly assigned to receive 24 weeks' treatment with 2 μg/day paricalcitol or placebo. Primary endpoint was change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Zhang et al showed that the beneficial effect of 1,25-dihydroxyvitamin-D3 in rat liver Tx involves the reduction of proinflammatory pathways [34] pointing to an active immunomodulatory role of 1,25-dihydroxyvitamin-D3 in improving the outcome. Consistently, administration of 1,25-dihydroxyvitamin-D3 or an analogon to patients receiving renal Tx was found to reduce the risk of adverse events [31,37]. Patients with unrelated donors versus patients with sibling donors.…”
Section: Discussionmentioning
confidence: 89%
“…Zhang et al showed that the beneficial effect of 1,25-dihydroxyvitamin-D3 in rat liver Tx involves the reduction of proinflammatory pathways [34] pointing to an active immunomodulatory role of 1,25-dihydroxyvitamin-D3 in improving the outcome. Consistently, administration of 1,25-dihydroxyvitamin-D3 or an analogon to patients receiving renal Tx was found to reduce the risk of adverse events [31,37]. Patients with unrelated donors versus patients with sibling donors.…”
Section: Discussionmentioning
confidence: 89%
“…Cholecalciferol supplementation failed to demonstrate renoprotection in prospective study [88]. However, in a recent prospective placebocontrolled study, paricalcitol ameliorated proteinuria in KTRs [89].…”
Section: Vd Pleiotropy After Kt: Proteinuria and Renal Protectionmentioning
confidence: 93%
“…We performed an investigator-initiated, observational, cross-sectional study of adult deceased donor kidney transplant recipients that completed the ‘Paricalcitol versus placebo for reduction of proteinuria in kidney transplant recipients: a double-blind, randomized controlled trial’ ( ClinicalTrials.gov , number NCT01436747 ) [ 14 ]. Briefly, between July of 2012 and October of 2014 the Paricalcitol trial recruited a national cohort of adult kidney transplant recipients with stages 1–4 chronic kidney disease (CKD) and residual proteinuria more than 3 months after transplant.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were urinary PCR ≥20 mg/mmol despite optimization of the single-agent renin-angiotensin-aldosterone system blockade and an estimated glomerular filtration rate (eGFR) ≥15 mL/min/1.73m 2 . The study included a 12-week screening phase followed by a 24-week randomized treatment period and an 8-week follow-up after treatment withdrawal [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation